2009
DOI: 10.1038/nmat2470
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear transport in semiconducting polymers at high carrier densities

Abstract: Conducting and semiconducting polymers are important materials in the development of printed, flexible, large-area electronics such as flat-panel displays and photovoltaic cells. There has been rapid progress in developing conjugated polymers with high transport mobility required for high-performance field-effect transistors (FETs), beginning with mobilities around 10(-4) cm(2) V(-1) s(-1) to a recent report of 1 cm(2) V(-1) s(-1) for poly(2,5-bis(3-tetradecylthiophen-2-yl)thieno[3,2-b]thiophene) (PBTTT). Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
95
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 18 publications
8
95
1
Order By: Relevance
“…These results indicate that PF or Schottky mechanisms may be valid above 200 K for d ≥ 16 nm, where a voltage-dependent E a is observed (Table 1). PF transport has been proposed for organic semiconductors across distances greater than studied here, and is consistent with observed E dependence (46)(47)(48)(49).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results indicate that PF or Schottky mechanisms may be valid above 200 K for d ≥ 16 nm, where a voltage-dependent E a is observed (Table 1). PF transport has been proposed for organic semiconductors across distances greater than studied here, and is consistent with observed E dependence (46)(47)(48)(49).…”
Section: Resultssupporting
confidence: 89%
“…Given that classical mechanisms are not consistent with the BTB JV behavior, we note a few recent observations of field-driven mechanisms for transport in much thicker organic films (>100 nm) (46)(47)(48)(49). Whereas transport dimensions and bias voltages were much larger than the 4.5-22-nm range studied here, a linear dependence of ln J vs. E 1/2 was observed, as was T-independent conductance at low T. Although the mechanism is controversial, these observations were attributed to field-assisted hopping (46,48), field-assisted tunneling (47,48), multistep tunneling (47), or behavior similar to a Luttinger liquid (49). For the case of polythiophene thin-film transistors, a transition from PF-like behavior at room temperature to temperature-independent fieldemission hopping with an E 1/2 dependence at low temperature was reported (48).…”
Section: Resultsmentioning
confidence: 78%
“…Numerous experiments, however, have shown that the conductivity at low temperatures is finite [2][3][4][5][6] . The breakdown of the semi-classical approaches at low temperatures is due to quantum mechanical zero-point energy of the system.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results have included the realization of high carrier mobilities approaching 1 cm 2 /Vs in semicrystalline films of poly(2,5-bis(3-alkylthiophen-2-yl)thieno(3,2-b)thiophene) (pBTTT) 1 and the observation of nonlinear, metallic transport at high carrier concentrations 2 which can be described in terms of a one-dimensional Luttinger liquid 3 . Charge transport is usually probed by electrical measurements over a length scale of several micrometers using field-effect transistor (FET) structures.…”
mentioning
confidence: 99%